2014
DOI: 10.1016/j.apgeog.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the spatial patterns of fire density in Southern Europe using Geographically Weighted Regression

Abstract: The spatial patterns of fire occurrence were analyzed in two regions of Southern Europe, focusing on the long-term factors that influence fire distribution. The relationship between fire occurrence and the physical and anthropogenic variables collected was investigated with Geographically Weighted Regression (GWR) and the results were compared with Ordinary Least Squares (OLS). Local patterns of the significant variables were explored and a strong spatial variability of their explanatory power was revealed. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 58 publications
5
74
0
11
Order By: Relevance
“…"Arrolamento Geral de Gados e Animais de Capoeira" : 1934, 1955and 1970"Recenseamento Agrícola do Continente": 1989, 1999, Instituto Nacional de Estatística of the Piodão and Pomares parishes, respectively) ( Figure 7). Several studies confirm that this land cover is one of the types most seriously affected by wildfires (Nunes et al 2005;Sebastián-López et al 2008;Catry et al 2009;Moreira et al 2009;Bajocco and Ricotta 2008;Nunes 2012;Carmo et al 2011;Oliveira et al 2012;Ganteaume and Jappiot, 2013;Oliveira 2014;Nunes et al 2016). Conversely, Nunes et al (2016) found that in Portugal at municipal level, traditional activities based on agriculture, grazing and forestry seem to reduce the burnt area, suggesting that the survival of Mediterranean silvopasture activities reduces the frequency and impact of forest fires.…”
Section: Social and Economic Changesmentioning
confidence: 96%
“…"Arrolamento Geral de Gados e Animais de Capoeira" : 1934, 1955and 1970"Recenseamento Agrícola do Continente": 1989, 1999, Instituto Nacional de Estatística of the Piodão and Pomares parishes, respectively) ( Figure 7). Several studies confirm that this land cover is one of the types most seriously affected by wildfires (Nunes et al 2005;Sebastián-López et al 2008;Catry et al 2009;Moreira et al 2009;Bajocco and Ricotta 2008;Nunes 2012;Carmo et al 2011;Oliveira et al 2012;Ganteaume and Jappiot, 2013;Oliveira 2014;Nunes et al 2016). Conversely, Nunes et al (2016) found that in Portugal at municipal level, traditional activities based on agriculture, grazing and forestry seem to reduce the burnt area, suggesting that the survival of Mediterranean silvopasture activities reduces the frequency and impact of forest fires.…”
Section: Social and Economic Changesmentioning
confidence: 96%
“…Usually, lower elevation (Kalabokidis et al 2007;Sebastián-López et al 2008;Kwak et al 2012;Narayanaraj and Wimberly 2012;Liu and Wimberly 2015) and smaller slope gradient (Preisler et al 2004;Syphard et al 2008;Dondo Bühler et al 2013;Oliveira et al 2014;Argañaraz et al 2015) increase HCF occurrence. Since surface temperature and humidity are affected by terrain, these may be reflecting climatic conditions.…”
Section: Predictors For Long-term Studiesmentioning
confidence: 99%
“…Topography is considered to be an important factor that influences forest fires because topographic properties affect distributions of vegetation and local climate such as wind speeds [11,12,31,32]. Therefore, a Digital Elevation Model (DEM) was generated using national topographic maps at a scale of 1:25,000.…”
Section: Fire Ignition Factorsmentioning
confidence: 99%